Increased inclination towards herbal preparations as immunity booster among young adults in the times of pandemic: A cross-sectional study - Aayushi Rastogi; Arti Nigam; Shantanu Mandal; Sunayana Nath; Rachna Kapila (Wolters Kluwer Medknow Publications, 2022)
Introduction: With the lack of evidence-based specific therapy for COVID-19, the prevention against the infection and boosting the body's immunity is the only option. Experts have suggested the use of herbal plants to boost the immunity; however, the use and acceptance of herbal medicinal plants among young adults are not known. The present study is aimed at assessing the use of herbal medicinal preparations as immunity booster among young adults during the times of COVID-19 pandemic. Methods: A cross-sectional study was conducted among college-going students during October 23-31, 2020. A Google form was circulated to the target group through the private and institutional networks during the study period. The questionnaire consisted of questions related to past, current, and future use of the herbal medicinal preparations. Data were extracted in MS-Excel. Univariate analysis and logistic regression was performed using the SPSS software version 21. Results: A total of 318 participants with a mean age of 20.5 ± 2.1 and approximately 79% females were included in the analysis. Of the total, 65.7% participants stated some use of herbal preparations as the immunity booster during the pandemic. Type of family, monthly income of the family, and state of residence were not found to be significantly associated with the use of herbal medicinal plants during the pandemic, whereas the past use of herbal medicines, participants who considered herbal medicinal plants to be effective and safe were found to be significantly associated with the use of herbal preparations during the pandemic. Conclusion: A significantly large proportion of young adults are using herbal medicinal plants as immunity booster during the pandemic indicating inclination toward traditional medicines.